Identification, molecular characterization and factors associated with occurrences of Cryptosporidium spp. in calves on dairy farms in Brazil - Oliveira,Juliana Silva de (2021)
Abstract Cattle are an important source of zoonotic species of Cryptosporidium for humans. The aim of this study was to investigate the presence of Cryptosporidium, identify the species and determine the risk factors relating to environment, animals and management among dairy calves in eight Brazilian states. A total of 408 fecal samples from calves aged 1-60 days were analyzed. An epidemiological questionnaire was completed. Sample screening was performed using Ziehl-Neelsen technique and the positive samples were subjected to nested PCR. Cryptosporidium species were identified by means of the PCR-RFLP technique, using SSPI, ASEI and MBOII enzymes. The Ziehl-Neelsen technique showed that 89.7% (35/39) of the farms and 52.9% (216/408) of the samples were positive. Through nested PCR, these protozoa were detected in 54.6% of the samples. The 56 samples subjected to PCR-RFLP presented Cryptosporidium parvum. There was higher prevalence of the parasite in animals aged 7 to 28 days (62.6%). Diarrhea, ages between seven and 28 days and a spring water source were factors associated with the risk of infection. The calf hutch-type management system was associated with reduced infection. These findings demonstrate the high level of Cryptosporidium spp. circulation in cattle herds and the predominance of the species C. parvum.